Environmental Preferences and Concerns of Recreational Road Runners - Schuurman, Nadine; Rosenkrantz, Leah; Lear, Scott A. (International journal of environmental research and public health, 2021)
Recreational road running is growing in popularity and has been linked to numerous mental and physical health benefits. However, we know little about what environmental preferences or concerns runners have regarding participation in the sport, and whether differences exist across age and gender. We conducted a cross-sectional survey on recreational road runners to investigate the type of built and natural environments road runners prefer, as well as the safety and health concerns that may affect runners’ choice of environment. Responses were analyzed by age and gender. A total of 1228 road runners responded to the survey; 59.6% of respondents were women and 32.1% of respondents were men. Most respondents preferred to run on asphalt or sidewalk surfaces, and preferred well-lit, tree-lined routes. Major concerns for both men and women include animals and dangerous road conditions. Men and women differed significantly in their responses to the importance of running around others and their primary concerns while running. Results of this study serve to deepen our understanding of recreational road runners’ environmental preferences and concerns, providing valuable information for public health officials and city planners alike. This information must be considered if we are to continue to encourage uptake of running as a sport and reap its health effects.